1992
DOI: 10.1007/bf00442539
|View full text |Cite
|
Sign up to set email alerts
|

Keratinolysis by Absidia cylindrospora and Rhizomucor pusillus: biochemical proof

Abstract: Absidia cylindrospora and Rhizomucor pusillus causal agents of phycomycoses, were cultured on sterile natural keratins in a mineral solution and the keratin degradation products analyzed. The excess of sulphur was removed by oxidation to inorganic sulphate and thiosulphate, which were the main products of sulphitolysis of keratin. The proteolytic activity of the two fungi depended on the nature of the keratin substrate. Human scalp hair was the most favoured keratin substrate by both the fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Proteolytic activity has been demonstrated for another species of Absidia. Rajak et al (377) showed that A. cylindospora degrades keratin, with human scalp hair being the most favored keratin substrate.…”
Section: General Disease Manifestationsmentioning
confidence: 99%
“…Proteolytic activity has been demonstrated for another species of Absidia. Rajak et al (377) showed that A. cylindospora degrades keratin, with human scalp hair being the most favored keratin substrate.…”
Section: General Disease Manifestationsmentioning
confidence: 99%
“…Most research on the biodegradation of keratin has been carried out with dermatophytic (Deshmukh and Agrawal, 1985;Evans and Hose, 1975;Kunert, 1989) and nondermatophytic (Rajak et al, 1991(Rajak et al, , 1992 fungi and actinomycetes (Kunert, 1989;Noval and Nickerson, 1959), and the work with bacterial species has been little. The results obtained by Noval and Nickerson (1959) and Kunert (1989) with Streptomyces fradiae revealed that the degradation of hard keratins is due not only to extracellular protease (keratinase); it is always accompanied by the denaturation of keratin substrate by direct reduction, proteolysis, and finally by the marked alkalinization of the medium.…”
mentioning
confidence: 99%
“…Cysteine is the major amino acid in keratins (18). Several keratinolytic microorganisms have been characterized, mostly bacteria of the genus Bacillus (12,23) or Streptomyces (14,17) and saprophytic and dermatophilic fungi (19,21). However, a distinction should be made between initial disintegration of complex keratinous organs, such as chicken feathers, into smaller substructures and the complete dissolution of the molecular keratin.…”
mentioning
confidence: 99%